Analysis of Judgement on Cancellation of Bankruptcy of Intidana Saving and Loan Cooperative (Review of the Authority to File for Bankruptcy and PKPU against Cooperatives) - Anik Triharyani; Krista Yitawati; Arini Wildaniyati; Retno Iswati; Tanawat Sirichai; Sarjiyati (Jurnal Jurisprudence, 2023)
ABSTRACT Purpose: This scientific paper aims to analyze the review of the cancellation of the Intidana Cooperative bankruptcy associated with the authority to submit bankruptcy and PKPU to the cooperative. Methodology: Using normative legal research methods, this study examined primary legal materials, including Law Number 37 of 2004 concerning Bankruptcy and PKPU, Law Number 25 of 1992 concerning Cooperatives, and Decision Number 43 PK/Pdt.Sus-Pailit/2022, as well as secondary journals, books, and scientific publications related to cooperative bankruptcy. Results: Bankruptcy proceedings against cooperatives do not have any special requirements, like those against other institutions such as banks, securities companies, stock exchanges, clearing and guarantee agencies, and other institutions. In this case, a cooperative can be petitioned for bankruptcy in the Commercial Court if it has two or more creditors and against whom a debt that is due and collectible has not been paid. The application can be filed by 2 (two) parties, namely the cooperative itself as the debtor and its creditors. The absence of regulations governing the mechanism for filing for bankruptcy in cooperatives has a negative impact on the sustainability of cooperatives. Currently, many problematic cooperatives are filing for bankruptcy and PKPU. One of the problematic cooperatives that the authors are currently studying is the Intidana Cooperative. To overcome the problems in these troubled cooperatives, the government issued SEMA Number 1 of 2022 on the Special Civil Chamber Law Formulation regarding Bankruptcy and Suspension of Debt Payment Obligations for Cooperatives, where applications for bankruptcy and PKPU statements against cooperatives can only be submitted by the Minister in charge of government affairs in the field of cooperatives, i.e., the Minister of Cooperatives and SMEs and Cooperatives that run the business of Microfinance Institutions whose licenses are from OJK can only be submitted by OJK. Applications of the study: The government is expected to immediately make changes to the Bankruptcy Law and the Cooperatives Law in terms of the mechanism for filing bankruptcy and PKPU for cooperatives, determining clear and firm boundaries between open loop and close loop cooperatives, and where OJK will supervise cooperatives that carry out financial services business activities. Novelty/Originality of this study: Analyzing the decision of the judge's cancellation of the Intidana Cooperative Bankruptcy in the Decision of Reconsideration is associated with the authority to submit bankruptcy and PKPU in SEMA Number 1 of 2022. Keywords: Decision, Bankruptcy, Cooperative.   ABSTRAK Tujuan: Tulisan ilmiah ini bertujuan untuk menganalisis kajian pembatalan pailit Koperasi Intidana terkait dengan kewenangan mengajukan pailit dan PKPU kepada koperasi. Metodologi: Dengan menggunakan metode penelitian hukum normatif, penelitian ini mengkaji bahan hukum primer, antara lain Undang-Undang Nomor 37 Tahun 2004 tentang Kepailitan dan PKPU, Undang-Undang Nomor 25 Tahun 1992 tentang Perkoperasian, dan Putusan Nomor 43 PK/Pdt.Sus-Pailit/2022, serta jurnal sekunder, buku, dan publikasi ilmiah yang berkaitan dengan kepailitan koperasi. Temuan: Perkara pailit terhadap koperasi tidak memiliki persyaratan khusus, seperti terhadap lembaga lain yakni bank, perusahaan sekuritas, bursa efek, lembaga kliring dan penjaminan, dan lembaga lainnya. Dalam hal ini, koperasi dapat dimohonkan pailit di Pengadilan Niaga jika mempunyai dua atau lebih kreditur dan terhadapnya suatu utang yang telah jatuh tempo dan dapat ditagih belum dibayar. Permohonan dapat diajukan oleh 2 (dua) pihak, yaitu koperasi itu sendiri sebagai debitur dan krediturnya. Tidak adanya peraturan yang mengatur tentang mekanisme pengajuan pailit pada koperasi berdampak negatif terhadap keberlangsungan koperasi. Saat ini, banyak koperasi bermasalah yang mengajukan pailit dan PKPU. Salah satu koperasi bermasalah yang sedang dikaji oleh penulis adalah Koperasi Intidana. Untuk mengatasi permasalahan pada koperasi bermasalah tersebut, pemerintah menerbitkan SEMA Nomor 1 Tahun 2022 tentang Perumusan Undang-undang Kamar Perdata Khusus tentang Kepailitan dan Penundaan Kewajiban Pembayaran Utang Koperasi, dimana permohonan pailit dan pernyataan PKPU terhadap koperasi hanya dapat diajukan oleh Menteri yang menyelenggarakan urusan pemerintahan di bidang koperasi, yaitu Menteri Koperasi dan UKM yang menyelenggarakan usaha Lembaga Keuangan Mikro, dimana izin dari OJK hanya dapat diajukan oleh OJK. Kegunaan: Pemerintah diharapkan segera melakukan perubahan terhadap UU Kepailitan dan UU Koperasi dalam hal mekanisme pengajuan pailit dan PKPU bagi koperasi, penetapan batasan yang jelas dan tegas antara koperasi open loop dan close loop, dan keberadaan OJK akan mengawasi koperasi yang melakukan kegiatan usaha jasa keuangan. Kebaruan/Originalitas: Menelaah Putusan Hakim Pembatalan Pailit Koperasi Intidana dalam Putusan Peninjauan Kembali dikaitkan dengan kewenangan mengajukan Pailit dan PKPU dalam SEMA Nomor 1 Tahun 2022.  Kata kunci: Putusan, Pailit, Koperasi